Kajian Pustaka: Dampak Media Sosial Terhadap Kesehatan Mental Remaja - Evita Christy (Jurnal JURISTIC, 2025)
Social media has become an integral part of teenagers' lives in today's digital age. The use of platforms such as Instagram, TikTok, and WhatsApp provides a space for socializing, self-expression, and obtaining information. However, behind these benefits, social media also has a significant negative impact on the mental health of adolescents. This study aims to examine the influence of social media on the psychological aspects of adolescents, including increased anxiety, depression, body image disorders, and low self-esteem. The research method used is a literature study of various academic journals and empirical data related to adolescent behavior on social media. The results show that excessive use of social media can trigger social pressure due to unrealistic social comparisons, cyberbullying, and digital addiction. Adolescents tend to experience sleep disorders, stress, and difficulties in building healthy social interactions in the real world. This study concludes that families, schools, and communities play an important role in providing digital literacy education and guiding adolescents in the wise use of social media so that the negative impacts on mental health can be minimized. Education and supervision are key to creating a safe and healthy digital environment for adolescent development.